Is Workplace Training more Beneficial for Vocationally Educated Workers? : A Comparison Between England and Germany - Icardi, Rossella [Verfasser] (My University, 2015)
There is evidence that participation in workplace training has a positive effect on wages; however, it is unknown whether training returns differ across different types of educational attainment. This exploration is relevant because it may indicate a way to redress wage gaps in the labour market. Using the German Socio Economic Panel and the British Household Panel Survey, this paper looks at individuals educated at the secondary level in Germany and England and examines whether workplace training has a positive association with wages for them and, if so, whether the returns vary by their type of education, vocational or general. This study uses a difference-in-differences approach and its combination with propensity score matching to address the problem of training endogeneity. Results indicate that training returns differ across countries and by type of educational attainment; however, any significant 'effects' disappear when selection of trainees is taken into account demonstrating the importance of model choice on results found." (Author's abstract)
Keywords: L 2.1 Lernformen; S 4.3.6 Human Capital; T 1.5 International vergleichende Berufsbildungsforschung; Lernen am Arbeitsplatz; Bildungsertrag; Einkommen; Sozioökonomisches Panel; Internationaler Vergleich; England; Bundesrepublik Deutschland